PEMODELAN DEMAM BERDARAH DENGUE DENGAN METODE REGRESI LOGISTIK BINER DI KOTA TOBELO - Trifena Punana Lesnussa; Samsul Bahri Loklomin (VARIANCE: Journal of Statistics and Its Applications, 2021)
One of the infectious diseases that is still a public health problem in Indonesia, especially in North Maluku, is Dengue Hemorrhagic Fever (DHF). This study aims to model DHF cases in Tobelo City, North Halmahera Regency. The results showed that in Tobelo City there were 103 DHF sufferers and 2 deaths occurred. The method used in this research is binary logistic regression to model DHF cases. Binary logistic regression is a data analysis method used to find the relationship between the binary response variable (y) and the predictor variable (x). In this study, the binary response variable used was DHF sufferers. The predictor variables used were gender, education level and access to health. The results of the analysis using the binary logistic regression method obtained a strong correlation between the response variable y and all the predictor variables x and the coefficient of determination obtained from the model was 52%.